Getting the facts right on born globals - Shon Ferguson; Magnus Henrekson; Louise Johannesson (Research Institute of Industrial Economics (IFN), 2018)
Policymakers in several countries have recently taken steps to promote the rapid export expansion of small- and medium-sized enterprises (SMEs). The goal of these policies has been to create successful export-intensive firms, which are often referred to as born globals. These measures are motivated by studies claiming that born global firms are disproportionately important for job creation and economic growth. Using detailed register data on the universe of Swedish manufacturing firms born between 2001 and 2008, we find that born globals are a very small group of firms whose long-run size and growth do not outperform other exporting firms. Thus, the notion that born globals are superior to firms that follow a more gradual internationalization process, a conclusion largely based on case studies and surveys, does not withstand scrutiny. Policymakers must therefore be aware that encouraging more born globals need not necessarily lead to large benefits for the overall economy, especially in terms of employment.
Keywords: F14; F23; L25; M13; 330; Born globals; Exporting; Firm growth; Globalization; Job creation